Glymphatic Cerebrospinal Fluid and Solute Transport Quantified by MRI and PET Imaging. (15th October 2021) - Benveniste, Helene; Lee, Hedok; Ozturk, Burhan; Chen, Xinan; Koundal, Sunil; Vaska, Paul; Tannenbaum, Allen; Volkow, Nora D.
Highlights: DCE-MRI is a robust imaging platform for quantifying glymphatic transport. Glymphatic transport and CSF flow dynamics is dependent on body posture. T1 mapping can quantify glymphatic transport and cervical lymph node drainage concurrently. Glymphatic transport kinetics are heterogenous across brain regions. Regularized optimal mass transport analysis incorporates advective as well as diffusion terms. Glymphatic transport can be measured by positron emission tomography. Abstract: Over the past decade there has been an enormous progress in our understanding of fluid and solute transport in the central nervous system (CNS). This is due to a number of factors, including important developments in whole brain imaging technology and computational fluid dynamics analysis employed for the elucidation of glymphatic transport function in the live animal and human brain. In this paper, we review the technical aspects of dynamic contrast enhanced magnetic resonance imaging (DCE-MRI) in combination with administration of Gd-based tracers into the cerebrospinal fluid (CSF) for tracking glymphatic solute and fluid transport in the CNS as well as lymphatic drainage. Used in conjunction with advanced computational processing methods including optimal mass transport analysis, one gains new insights into the biophysical forces governing solute transport in the CNS which leads to intriguing new research directions. Considering drainage pathways, we review the novel T1 mapping technique for quantifying glymphatic transport and cervical lymph node drainage concurrently in the same subject. We provide an overview of knowledge gleaned from DCE-MRI studies of glymphatic transport and meningeal lymphatic drainage. Finally, we introduce positron emission tomography (PET) and CSF administration of radiotracers as an alternative method to explore other pharmacokinetic aspects of CSF transport into brain parenchyma as well as efflux pathways.